Effect of Friedel–Crafts reaction on the thermal stability and flammability of high‐density polyethylene/brominated polystyrene/graphene nanoplatelet composites. Issue 10 (17th February 2014) - Ran, Shiya; Guo, Zhenghong; Han, Ligang; Fang, Zhengping
<x xml:space="preserve">Abstract</x> Brominated flame‐retarded high‐density polyethylene (HDPE) composites containing graphene nanoplatelets (GNPs) were prepared via melt blending. A Lewis acid catalyst, anhydrous aluminium chloride (AlCl3), was added to initiate Friedel–Crafts reaction for promoting the dispersion of the GNPs in the polymer matrix. Transmission electron microscopy images and Raman spectroscopy revealed that the GNPs were partly unfolded and the domains became smaller in the presence of AlCl3. Limiting oxygen index and microscale combustion calorimetry showed that the incorporation of AlCl3 into HDPE reduced flammability and slowed down the heat release rate. Thermogravimetric analysis and char residue measurements proved that a uniform dispersion of GNPs was crucial for forming a continuous and compact carbon layer, thus isolating the underlying materials from flame and preventing heat transfer. Rheological and mechanical tests indicated that interfacial adhesion between polymer chains and GNPs was enhanced. © 2014 Society of Chemical Industry